2013
DOI: 10.1002/jgra.50220
|View full text |Cite
|
Sign up to set email alerts
|

Electron source at the outer boundary of the radiation belts: Storm time case

Abstract: [1] We examine the strength of the electron source at the outer boundary of the radiation belts using multisatellite observations from Time History of Events and Macroscale Interactions during Substorms during one moderate geomagnetic storm. The electron phase space density (PSD) as a function of the first adiabatic invariant for an equatorially mirroring population over a broad energy range is used to determine the source strength. It is found that the source strength from dipolarization at the outer boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(64 reference statements)
2
2
0
Order By: Relevance
“…The main conclusion of this study is that we have confirmed here the previous results of Taylor et al. (2004) and Lui (2013) that Earth's magnetotail is capable of rapidly and efficiently accelerating electrons to relativistic levels and PSD(M) that exceed those in the outer radiation belt (assuming transport that conserves the first adiabatic invariant). The combination of simultaneous observations using well‐calibrated data from MMS and RBSP leaves no uncertainty that the answer to the question “Can Earth's magnetotail plasma sheet produce a source of relativistic electrons for the radiation belts?” is: yes, it can.…”
Section: Interpretation Consequences and Conclusionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main conclusion of this study is that we have confirmed here the previous results of Taylor et al. (2004) and Lui (2013) that Earth's magnetotail is capable of rapidly and efficiently accelerating electrons to relativistic levels and PSD(M) that exceed those in the outer radiation belt (assuming transport that conserves the first adiabatic invariant). The combination of simultaneous observations using well‐calibrated data from MMS and RBSP leaves no uncertainty that the answer to the question “Can Earth's magnetotail plasma sheet produce a source of relativistic electrons for the radiation belts?” is: yes, it can.…”
Section: Interpretation Consequences and Conclusionsupporting
confidence: 90%
“…In contrast, previous analyses by Taylor et al. (2004) and Lui (2013) indicated that, at least sometimes, there may be a sufficient source of M > 300 MeV/G electrons within the magnetotail plasma sheet. While simulations using advanced models have demonstrated how magnetotail reconnection and corresponding substorm activity can result in injections of relativistic electrons directly into the outer radiation belt (Eshetu et al., 2019; Sorathia et al., 2018), injections of >300 keV electrons are rarely observed at and inside of geosynchronous orbit ( L * < ∼6; e.g., Baker et al., 1978, 1998; Birn et al., 1998).…”
Section: Introductionmentioning
confidence: 75%
“…[] used observations from THEMIS to show that the phase space density (PSD) of energetic electrons associated with current disruption/dipolarization (CDD) events during nonstorm periods outside the radiation belts is high enough to account for the population of relativistic electrons in the outer radiation belt if they could be transported without significant loss. This study was followed by another study [ Lui , ] showing similar results for the 5 April 2010 magnetic storm previously examined for different aspects of the storm by others [e.g., Connors et al ., ; McComas et al ., ; Goldstein et al ., , ; Clilverd et al ., ]. These two studies by Lui emphasized that the results do not dispute the importance of an internal source in the production of energetic electrons in the radiation belts during geomagnetic storms.…”
Section: Introductionsupporting
confidence: 72%
“…Therefore, magnetic moments ( μ ) are conserved and of course the μ uc of injected electrons at different L shells are equal. Recently, based on multisatellite observations from THEMIS, Lui () and Lui et al (, ) demonstrated that the source strength of energetic electrons associated with dipolarization at the outer radiation belt boundary during both quiet and storm periods is adequate to account for the electron intensity in the outer radiation belt, if electrons could be transported inward without significant loss. Therefore, it is possible that injected electrons observed in the inner magnetosphere come from higher L shells.…”
Section: Discussionmentioning
confidence: 99%